A Tool to Support Anti-Crisis Training as an Example of Dual-Use of IT Technology - Wojciech KULAS; Zbigniew TARAPATA (Communications of International Proceedings, 2020)
In the paper, the authors presented the concept and elements of implementation of the subsystem to support the training process of operators of the anti-crisis system. It was made in the form of emulators of hazard monitoring systems for the needs of an IT system supporting the analysis of threats in the form of CBRN (Chemical, Biological, Radiation, Nuclear) contamination, forecasting their effects and alerting the population. The genesis of building the emulator subsystem is the need to provide a tool to support the training process of people involved in the activities of the National System of Detection of Contamination and Alarming (KSWSiA) in Poland. However, the emulators designed in this way can also be used as a tool to support the development of emergency procedures and to support the software development process. Emulators were proposed as pure IT tools, run in the same hardware environment as the constructed system. A constructive simulation was chosen as the emulation method, but reduced to a simple, determined data delivery in accordance with the previously prepared scenario.
Keywords: Emulators; Support of Anti-Crisis Training; Software Development; Dual-Use of IT Technology.